If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8v + -8 + 2(3v + 6) = -2(v + 5) Reorder the terms: 8v + -8 + 2(6 + 3v) = -2(v + 5) 8v + -8 + (6 * 2 + 3v * 2) = -2(v + 5) 8v + -8 + (12 + 6v) = -2(v + 5) Reorder the terms: -8 + 12 + 8v + 6v = -2(v + 5) Combine like terms: -8 + 12 = 4 4 + 8v + 6v = -2(v + 5) Combine like terms: 8v + 6v = 14v 4 + 14v = -2(v + 5) Reorder the terms: 4 + 14v = -2(5 + v) 4 + 14v = (5 * -2 + v * -2) 4 + 14v = (-10 + -2v) Solving 4 + 14v = -10 + -2v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '2v' to each side of the equation. 4 + 14v + 2v = -10 + -2v + 2v Combine like terms: 14v + 2v = 16v 4 + 16v = -10 + -2v + 2v Combine like terms: -2v + 2v = 0 4 + 16v = -10 + 0 4 + 16v = -10 Add '-4' to each side of the equation. 4 + -4 + 16v = -10 + -4 Combine like terms: 4 + -4 = 0 0 + 16v = -10 + -4 16v = -10 + -4 Combine like terms: -10 + -4 = -14 16v = -14 Divide each side by '16'. v = -0.875 Simplifying v = -0.875
| 25+18=26x+24 | | 5x+54=9x+15 | | 4(7+x)= | | 1-2x=4x-41 | | h^2-21=60 | | 0.7x-0.2=8.3x+7.2 | | x+4+x+4= | | 6=64t^2+vot+ho | | 12+(5-y)=51 | | 12+(y+5)=26 | | f(x)=x^2-4x+4 | | c^2+6=0 | | -58-10x=90-45x | | 91-3x=3x+9 | | 5(y+4)=-2(3y-8)+y | | -6-9+(-4)= | | 3(5-2x)=-2(6-3x)-10x | | 2x^2-9x-3=9-9x | | -11-2x=-37-10x | | 2x+7=25-7 | | 6x+69=9x-6 | | 2(2+5)=3(x-10) | | 5/16x+3/8x=1/4x+2 | | x*x+6x=8 | | 5(3+2y)+4y=3 | | 230-3x=42x+5 | | 5x+31=5x+4 | | 7x+14-9x=20-13x+11x-6 | | (x+4)+(x+5)= | | 15-(3m+4)=2+4m-19 | | (x+5)(x-3)(x^2+1)=0 | | 13/3=y/8 |